2010
DOI: 10.1111/j.1365-2036.2010.04274.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: clarithromycin vs. levofloxacin in first‐line triple and sequential regimens for Helicobacter pylori eradication

Abstract: SUMMARY BackgroundHelicobacter pylori eradication rates with standard triple therapy have declined to unacceptable levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 38 publications
0
35
0
2
Order By: Relevance
“…22 However, a recent update of previous meta-analyses performed by a Cochrane Collaboration group23 found that the results obtained with the sequential regimen were clearly heterogeneous, and that several recently published studies were unable to demonstrate differences between sequential and standard triple therapy. So, although the overall mean eradication rate with the sequential regimen was nearly 90%, a tendency towards lower efficacy with this regimen was observed in the more recent studies 2427…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…22 However, a recent update of previous meta-analyses performed by a Cochrane Collaboration group23 found that the results obtained with the sequential regimen were clearly heterogeneous, and that several recently published studies were unable to demonstrate differences between sequential and standard triple therapy. So, although the overall mean eradication rate with the sequential regimen was nearly 90%, a tendency towards lower efficacy with this regimen was observed in the more recent studies 2427…”
Section: Introductionmentioning
confidence: 90%
“…The authors evaluated the efficacy of empiric concomitant therapy in a geographical area (Spain) where sequential therapy had previously proved inefficient (76% cure rate in a prior study24). Eradication rates for the concomitant regimen were 88% by per-protocol analysis and 85% by intention-to-treat analysis, and the authors concluded that in settings with high clarithromycin resistance (>5%–20%) and documented failure of sequential therapy, concomitant therapy may achieve acceptable eradication rates 50.…”
Section: Effects Of Different Variables On the Efficacy Of Concomitanmentioning
confidence: 99%
“…However, the eradication rates achieved with first-line levofloxacin-based treatments are not uniform. Some reports show improved efficacy with levofloxacin-based regimens in comparison to standard first-line therapy, whereas others have found equivalent or poorer responses [9], [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This was much higher than the eradication rate after 10 days of LBT using omeprazole and lansoprazole (72–83%) [13, 15, 16] and was comparable with that of LBT using esomeprazole (87–96%) [17, 18]. This suggests that ilaprazole may have unique properties and better pharmacokinetic and pharmacodynamic profiles compared with other PPIs.…”
Section: Discussionmentioning
confidence: 77%